A morphometric and molecular phylogenetic analysis of the African orchid genus Stenoglottis (Orchidaceae: Orchidoideae). (23rd March 2020) - Phillips, Dean P; Bytebier, Benny
Abstract: Stenoglottis is a small genus of forest orchids endemic to continental Africa. Nine taxa have so far been described, but species boundaries in the genus are problematic and several of these taxa are not widely accepted. In this study, taxon boundaries were investigated by means of a combination of morphometric and phylogenetic analyses, with the aim of resolving species-level relationships and identifying practical diagnostic characters. Sequence variation was low, particularly in plastid DNA ( atpI-atpH ), and Bayesian inference and maximum likelihood analyses of nuclear markers (ITS and ETS) did not resolve all of the putative taxa. Multivariate morphometrics (PCA, PCoA, cluster analysis) likewise did not support the recognition of all described Stenoglottis taxa, but they reliably distinguished some taxa that DNA data did not. Combined morphological and phylogenetic evidence supports the delimitation of five species and two varieties, for which characteristics of floral spurs, labella, leaves, bracts and auricles provide reliable diagnostic traits. These findings will form the basis of a taxonomic revision in which the proposed changes will be formalized.